An accelerated asynchronous distributed control for DFIG wind turbines and collection system loss minimization in waked wind farm - Wang, Pengda; Xiao, Jinxin; Huang, Sheng; Wu, Qiuwei; Zhang, Menglin; Wu, Xuan; Shen, Feifan; Ma, Kuichao (Applied energy, 2025)
A loss minimization method achieved by voltage control strategy for doubly-fed induction generator wind turbine generators and collection system in waked wind farm with an accelerated asynchronous distributed calculation scheme is proposed in this paper. With the model predictive control-based voltage control strategy used, the active power of generators and reactive power of rotor-side and grid-side converters can be coordinated, and thus the loss of wind turbines and collection system is minimized, which can improve the power generation of wind farm and service lifetime of wind turbines. In addition, a modified time-varying dynamic wake model is established to improve the accuracy of wake wind speed calculation. Further, the wake propagation process described by time delay is taken into consideration. Meanwhile, a correction method related to turbulence intensity is used to modify downstream wind speed. An asynchronous distributed calculation scheme is introduced to improve efficiency of solving the large-scale optimization problem, meanwhile strengthen the robustness to communication delay and failures. To further speed up the computation, the Nesterov acceleration strategy is introduced. Simulations show that compared to the traditional method, the proposed strategy reduces the loss and decreases the voltage by an average of 2.78 % and 11.84 % under the three wind directions, meanwhile owns stronger robustness under communication delay and failures with fewer iterations compared to traditional distributed calculation scheme. [Display omitted] •A loss minimization method for wind farm achieved by voltage control is proposed.•A modified time-varying dynamic wake model considering time delay is established.•A Nesterov-based accelerated asynchronous DCS is introduced to solve the large-scale optimization problem.•The total loss in WF is minimized meanwhile maintain feasible terminal voltage.•Results show the stronger robustness and faster calculation speed.